Evaluation of anti-cancer activity of Ruellia tuberosa on EAC induced mammary tumor - Vennapusa, Nagarjuna Reddy; Pkm, Nagarathna; Madanu, Divya (International Journal of Pharmacology and Toxicology, 2013)
Aim of the study was to study the  antitumor effect of Ruellia tuberosa. The  activity of methanolic extracts of 250, 500 mg/kg of Ruellia tuberosa leaves was evaluated against Ehrlich ascites carcinoma (EAC) tumor in mice. Acute and short-term toxicity studies were performed initially in order to ascertain the safety of methanolic extracts of Ruellia tuberosa. Tumour cells (1×106cells/mice) were injected into the right hind limb (thigh) of mammary tumour group animals subcutaneously and the tumour is allowed to develop for 11 days and the treatment is started from 12th day for a period of 20 days. The effect of methanolic extracts of Ruellia tuberosa on the growth of tumor, life span of EAC bearing hosts and simultaneous alterations in the hematological profile and histopathological profile were estimated. The methanolic extracts of Ruellia tuberosa showed decrease in tumor size, average body weight, and mean survival time thereby increasing life span of EAC tumor bearing mice. Hematological profile reverted to more or less normal levels in extracts treated mice. Histopathology has minimal effects when compared but a significant variation is seen.